2019
DOI: 10.1002/jctb.6089
|View full text |Cite
|
Sign up to set email alerts
|

A novel silica xerogel synthesized from volcanic tuff as an adsorbent for high‐efficient removal of methylene blue: parameter optimization using Taguchi experimental design

Abstract: BACKGROUND: In this study, silica xerogel was synthesized using volcanic tuff instead of expensive silica precursors at ambient pressure drying. The mesoporous silica xerogel with unique structural and textural properties was evaluated as an adsorbent for methylene blue (MB) removal from aqueous solution. Taguchi method was applied to optimize controllable factors (contact time, initial MB concentration, silica xerogel dose, temperature and pH) for MB removal. RESULTS:The temperature was determined as the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Table 3 shows a comparison of the adsorption capacity of MB by MZN with the reported data obtained from the various silica-based adsorbents. The reported adsorption capacity for MB by a wide variety of silica-based adsorbents, including PVDF/glass asprepared composite membrane [49], silica xerogel [27], pure silica [50], hollow silica [51], Ag/SiO 2 [52], and hydroxyl group silica aerogel [53], were in the range of 44.4-102 mg g −1 , respectively. In this study, the adsorption capacity of MB by MZN is better than most of the reported silica-based adsorbents, indicating that MZN is an excellent negative charged material for effective adsorption of positive charged MB in an aqueous solution.…”
Section: Adsorption Isotherm Of Mb By Mznmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 shows a comparison of the adsorption capacity of MB by MZN with the reported data obtained from the various silica-based adsorbents. The reported adsorption capacity for MB by a wide variety of silica-based adsorbents, including PVDF/glass asprepared composite membrane [49], silica xerogel [27], pure silica [50], hollow silica [51], Ag/SiO 2 [52], and hydroxyl group silica aerogel [53], were in the range of 44.4-102 mg g −1 , respectively. In this study, the adsorption capacity of MB by MZN is better than most of the reported silica-based adsorbents, indicating that MZN is an excellent negative charged material for effective adsorption of positive charged MB in an aqueous solution.…”
Section: Adsorption Isotherm Of Mb By Mznmentioning
confidence: 99%
“…A Taguchi optimization study like this should reduce energy consumption in resource-related industries. Several studies have been conducted to investigate the optimum process parameters to enhance adsorption capacity to remove methylene blue [27] and optimize Pb(II) ion adsorption on nanohydroxyapatite adsorbents [28]. However, different parameters (reaction agent ratio, temperature, time, and agent concertation) significantly affect the quality of the material process, which affects the efficiency of organic dye removal.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis procedure of silica xerogel consisted of three steps after pretreatment of the volcanic tuff [ 37 ]. The tuff was washed with 3 M HCl solution for 2 h at 60 °C to eliminate undesirable minerals.…”
Section: Methodsmentioning
confidence: 99%
“…As depicted in the figure, the pHpzc value for MIL-53 (Al) was calculated as 4.1. If the pH of the medium is below 4.1, the net adsorbent charge is positive, while above it is negative [24]. In this case, at the optimum pH value (pH=3.2) the adsorbent charge is positive.…”
Section: 𝑅 =mentioning
confidence: 96%